Biotechnology, trade, and hunger: IFPRI 2000-2001 Annual Report Essay - Díaz-Bonilla, Eugenio; Robinson, Sherman (International Food Policy Research Institute, 2003)
Number 2 in a series of IFPRI briefs on biotechnology and genetic resource policies. The briefs present syntheses and synopses of research conducted by a team from IFPRI's Environment and Production Technology Division and several collaborators. The team focuses on issues related to intellectual property rights, genetic resource management and conservation, biodiversity, and biotechnology.